2021
DOI: 10.1007/s10811-021-02609-7
|View full text |Cite
|
Sign up to set email alerts
|

Artificial biocrust establishment on materials of potash tailings piles along a salinity gradient

Abstract: Biocrust communities provide a pallet of ecosystem services, such as soil stabilization, altering of hydrological cycles and primary production, and often are the first colonizers of unvegetated surfaces during succession. Therefore, artificially establishing biocrusts can improve soil properties, for example, by stabilizing bare soil surfaces against erosion or by accumulating nutrients. In this study, the establishment of artificial biocrusts was tested for the restoration of potash tailings piles that resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…is used [ 57 ], which shows great abilities in concatenating soil particles as a pioneer microbe. Recently, similar approaches have been undertaken with eukaryotic green algae that were used as inoculum in order to colonize and stabilize potash piles [ 58 ]. However, the two Cyanocohniella strains are also suitable for such purposes and additionally have the advantage that they can fix atmospheric nitrogen, which enriches soil fertility and thus can speed up remediation processes.…”
Section: Discussionmentioning
confidence: 99%
“…is used [ 57 ], which shows great abilities in concatenating soil particles as a pioneer microbe. Recently, similar approaches have been undertaken with eukaryotic green algae that were used as inoculum in order to colonize and stabilize potash piles [ 58 ]. However, the two Cyanocohniella strains are also suitable for such purposes and additionally have the advantage that they can fix atmospheric nitrogen, which enriches soil fertility and thus can speed up remediation processes.…”
Section: Discussionmentioning
confidence: 99%
“…Biocrust species richness can promote soil biological functions by facilitating soil microbial colonization in salinized drylands in two ways: First, biocrusts facilitate nutrient cycling and soil organic matter inputs (Barger et al, 2016; Duran et al, 2021) and consequently enhance soil nutrient functions (Figure 4b). Second, biocrusts provide more favourable microsites by enhancing infiltration, soil water content (soil hydrological functions), and reducing soil salinity compared to adjacent saline bare soils (Kakeh et al, 2020; Sommer et al, 2021). Therefore, biocrusts indirectly relieve water and nutrient limitations and salinity stress for soil microbes and their activities (Delgado‐Baquerizo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The strong association between biocrust species richness and soil biological functions (Figure 4b) demonstrates that biocrusts promote soil microbial communities and microbial biomass (Su et al, 2021 4b). Second, biocrusts provide more favourable microsites by enhancing infiltration, soil water content (soil hydrological functions), and reducing soil salinity compared to adjacent saline bare soils (Kakeh et al, 2020;Sommer et al, 2021). Therefore, biocrusts indirectly relieve water and nutrient limitations and salinity stress for soil microbes and their activities (Delgado-Baquerizo et al, 2016).…”
Section: Influence Of Biocrust Richness On Soil Biological Functionsmentioning
confidence: 99%
“…Halotolerant algae produce a wide variety of secondary metabolites beneficial to salinized agriculture [23] and may be utilized in bioremediation [21,24,62], including desalination [63]. P. monallantoides, which was successfully used to grow young biocrusts on saline substrates from potash tailing heaps [26]. Hence, the soil desalinization with this genus is not purely conjectural.…”
Section: Salinity and Desiccationmentioning
confidence: 99%
“…While halotolerant algae have chiefly been used to bioremediate saline waters and salinized soils, crop yield increase is also a growing field in applied phycology [12,[23][24][25]. However, recent work has shown that some algae were able to form young biocrusts on hypersaline potash tailing heaps, with ramifications for salinity bioremediation [26][27][28]. Among the organisms isolated form salt heaps were Chloroidium ellipsoideum, the cyanobacterium Nostoc, representatives from Stichococcus and Pseudostichococcus [27].…”
Section: Introductionmentioning
confidence: 99%